Effect of Sex, Level and Period of Feed Restriction During the Starter Stage on Productivity and Carcass Characteristics of Ross 308 Broiler Chickens in South Africa - Novele, D.J.; Ng`Ambi, J.W.; Norris, D.; Mbajiorgu, C.A. (International Journal of Poultry Science, 2008)
The effects of sex, level and period of feed restriction during the starter period on productivity and carcass characteristics of Ross 308 broiler chickens were evaluated. A 2 (male and female chickens) x 3 (feeding levels: Ad-libitum, 75% and 50% of ad libitum) x 3 (restriction periods of 5, 7 and 9 days) factorial arrangement in a complete randomized design was used. The effects of interactions were not included in the results because earlier analyses including all the interactions showed that they were not important. Level and period of feed restriction during the starter stage had an effect (P<0.05) on live weight of the chickens at 21 days of age. Chickens on 75% ad libitum feeding attained complete live weight compensation with those on Ad-libitum feeding at the age of 42 days. However, chickens on 50% ad libitum feeding did not ‘catch-up’ with those on ad libitum feeding. Differences due to the period of feed restriction during the starter stage were maintained up to the age of 42 days. Male chickens had higher (P<0.05) live weights at 42 days of age. Abdominal fat pad was not affected (P>0.05) by level and period of feed restriction and sex of chickens at 42 days of age.